Malawi Engaging the Private Sector in Education : SABER Country Report 2015 - Baum, Donald Rey; De Brular, Laura Lewis (World Bank, Washington, DC, 2017)
This report presents an analysis of how effectively current policies in Malawi engage the private sector in primary and secondary education. The analysis draws on the engaging the private sector (EPS) framework, a product of the World Bank’s systems approach for better education results (SABER). SABER-EPS research in Malawi found that the net enrollment rate for primary education has increased significantly, to 89 percent, while secondary net enrollment rate remains low, at only 11 percent as of 2013 (the latest available data). At both the primary and secondary levels, quality, and equity are challenges. The private sector plays an increasingly significant role in education at both levels. Based on a review of existing policies, SABER-EPS offers the following recommendations for enhancing private sector engagement in the education sector in the country in order to meet the challenges of access, quality, and equity: (1) concentrate on improving the quality of learning outcomes by encouraging continuous improvement at the school level by means of school improvement planning and incentives; (2) empower parents by ensuring that they are given information on school quality that enables them to make informed choices and are not hindered by restrictive school selection criteria; and (3) create a regulatory environment that encourages greater supply of school places to help overcome constraints, particularly at the secondary level. The report provides an overview of SABER-EPS, followed by a description of the primary and secondary education system in Malawi with a focus on the private sector and government policies related to the private provision of education. The report then benchmarks Malawi’s policy environment utilizing the SABER-EPS Framework and offers policy options to enhance access and learning for all children in primary and secondary school.